2022
DOI: 10.3389/fonc.2022.949962
|View full text |Cite
|
Sign up to set email alerts
|

Primary intrathoracic liposarcomas: A clinicopathologic and molecular study of 43 cases in one of the largest medical centers of China

Abstract: IntroductionPrimary intrathoracic liposarcoma is extremely rare, and most published series lack genetic analyses. The aim of our study is to better understand the clinicopathologic and genetic features of these rare lesions.Materials and methodsForty-three primary intrathoracic liposarcomas were identified and most cases were analyzed by systematic genetic studies, including fluorescence in situ hybridization (FISH), whole-exome sequencing (WES), and Sanger sequencing.ResultsThis series included 27 males and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…11 Previous case reports or research on primary mediastinal DDL have shown that complete surgical excision was performed in almost all patients. 4,[11][12][13][14] As mentioned above, a total of 41 literature reported 95 cases of PMLs, Of them, histologic examination confirmed 21 cases of DDL, but only 3 cases of DDL in the posterior mediastinum had been reported, and as follows: Kentaro Miura et al 12 reported a 75-year-old man, who did not exhibit any symptoms, but chest CT showed a huge tumor (20 cm in diameter) in the posterior mediastinum, which projected on either side of the intrathoracic space, surgical resection was performed, pathology revealed DDL, and there was no recurrence at 3 months. Hejin P. Hahn et al 4 reported a 65-year-old man, whose chest CT showed a 17 cm huge tumor in the posterior mediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…11 Previous case reports or research on primary mediastinal DDL have shown that complete surgical excision was performed in almost all patients. 4,[11][12][13][14] As mentioned above, a total of 41 literature reported 95 cases of PMLs, Of them, histologic examination confirmed 21 cases of DDL, but only 3 cases of DDL in the posterior mediastinum had been reported, and as follows: Kentaro Miura et al 12 reported a 75-year-old man, who did not exhibit any symptoms, but chest CT showed a huge tumor (20 cm in diameter) in the posterior mediastinum, which projected on either side of the intrathoracic space, surgical resection was performed, pathology revealed DDL, and there was no recurrence at 3 months. Hejin P. Hahn et al 4 reported a 65-year-old man, whose chest CT showed a 17 cm huge tumor in the posterior mediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…CT and MRI (magnetic resonance imaging) are the main examination methods of the disease. On CT images is often characterized by uniform density or owe homogeneous low density lump, most do not appear calci cation, CT value between fat density, tumor border and clear, the shape is given priority to with class round, shallow part can present lobulated, locally connected with pleural basement, enhanced scan the margins or coated mild reinforcement, mass center usually without reinforcement, in addition, for large tumors, Local lesions such as hemorrhage, cystic degeneration and necrosis may occur, and some lesions may have invasive invasion of adjacent tissues [9,[13][14][15][16][17]. Although myxoid pleomorphic liposarcoma has many imaging features on CT ndings, it still lacks speci city.…”
Section: Discussionmentioning
confidence: 99%
“…Primary esophageal liposarcoma is commonly observed in elderly individuals over the age of 60 [5], albeit sporadically seen in adolescents. It exhibits a higher incidence in males compared to females.…”
Section: Clinical Manifestations and Pathological Featuresmentioning
confidence: 99%